Some theoretical aspects of the study of factors of labor motivation of civil servants - Abilmazhinov Т.Т. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with some theoretical aspects of the formation of labor motivation factors for civil servants. Based on the theoretical ideas of A. Maslow, the founder of the substantive motivation theories. Starting from the hierarchy of the needs A. Maslow offers a list of factors of labor motivation, where each group of needs gives rise to its own group of factors of any worker’s labor motivation. Specific features of labor activity of civil servants are analyzed, as well as personal characteristics of people who choose the profession of a civil servant were identified Such an analysis allowed the author to reveal internal motives that can motivate civil servants in the performance of their duties. Understanding the essence of civil servants’ internal motives enabled the author to give his priority assessment for certain factors of labor motivation of civil servants. Thus, the article not only covers the theory issues, but identifies the features inherent in the process of formation of labor motivation precisely among civil servants. The author also gives his vision of an approximate hierarchy of labor motivation factors of civil servants. The factors that play a primary role in the process of formation of labor motivation of civil servants are determined. According to the performed analysis, a system of labor motivation factors of civil servants was developed, the basis of which are factors arising from the basic human needs.